Group Motivational Interviewing for Adolescents at Risk of Internet Gaming Disorder: A Mixed-Methods Preliminary Evaluation. - Tse, Nick; Siu, Andrew; Tsang, Sharon; Jensen, Mark P. (Clinical Social Work Journal, 2026)
Internet gaming disorder (IGD) among adolescents is a widespread public health issue, with far-reaching negative impacts on adolescents' health and relationships with their families. This study evaluated the preliminary outcomes of a two-session Group Motivational Interviewing (GMI) programme designed to address the risk of IGD among students across primary, secondary, and university levels. Conducted in-person during short periods of time when schools were open during the COVID pandemic, the programme used experiential activities and guided discussions to (1) facilitate participants' reflection on time management, life goals, and gaming behaviours, and (2) cultivate readiness for change. Fifty-five students, aged 9 to 21, participated in the study, and outcomes were evaluated using a mixed-methods approach. Quantitative data tracked changes in severity of IGD symptoms, motivation for change, and time consumption on gaming, studying, and outdoor activities. The qualitative component involved analysing goal-setting worksheets to understand participants' motivations and potential barriers to change. Intervention fidelity was monitored using a modified checklist from the Assessment of Motivational Interviewing Groups– Observer Scale. Results revealed significant pre- to post-treatment reductions in gaming time and enhancements in motivation for change, but there was no significant change in the risks of IGD from baseline to post-treatment or three-month follow-up. Changes in the Contemplation Ladder indicated a sustained increase in motivation for change over the three-month follow-up. Furthermore, qualitative analysis revealed academic study as a crucial factor, serving both as a goal (improving academic results) and a barrier (alleviating academic stress) for changes in gaming behaviour. In conclusion, this study demonstrates that the two-session GMI programme is a feasible and potentially effective approach to engage students in reflecting on their gaming habits and promoting readiness for change. These preliminary results also provide support for conducting a full clinical trial on the effectiveness of the programme.